Interface fracture of micro-architectured glass: Inverse identification of interface properties and a novel analytical model. (October 2019) - Yadav, Upendra; Coldren, Mark; Bulusu, Praveen; Sain, Trisha; Ghosh, Susanta
Highlights: The properties of the interface are identified from the force-displacement data of mode one fracture experiment. A novel approximate analytical model is proposed to simulate the mode one fracture test. The analytical model involves the mixed mode cohesive fracture and the contact mechanics at the interface in addition to the elastic deformation of teeth. Present FE model has revealed important insights about the stress fields and the fracture process. Abstract: Recently, it is demonstrated that bio-inspired interlocking micro-architectures within a brittle material can increase its ductility and fracture toughness remarkably. Despite showing tremendous promise, there is a lack of computational and analytical models for these interlocked systems to simulate opening-mode fracture behavior. Besides, due to curved geometry of the interface its properties are difficult to obtain from experiments alone. In the present paper the effective thickness, cohesive and contact properties of the interface, are inversely identified from the experimental data by developing and using a finite element (FE) model as a forward solver. The identification is challenging due to the fact that the influences of these parameters on the mechanics are interdependent. Present FE model has revealed important insights about the stress fields and the interface fracture process. Further, a novel approximate analytical model is derived to simulate the complete pullout response of the interlocking teeth, which involves the mixed mode cohesive fracture and the contact mechanics at the interface in addition to elastic deformation of the teeth. The analytical model is derived independently without any phenomenological input from the experiments or the finite element simulations. However, the predictions by the analytical model match accurately with both experiments and the finite element simulations. It is expected that the proposed experimentally validated, predictive computational and analytical models of interlocking micro-architectured materials would generate insights into their complex failure process and enable their performance optimization for large-scale applications.